Internal marketing strategies in state universities in Zimbabwe: a case of Midlands State University - Mupemhi, Shepherd; Mupemhi, Ronicah (International Journal of Management and Business Studies, 2016)
The Midlands State University (MSU) was established in 1999 through an Act of the Parliament of Zimbabwe. It is one of the nine state universities in Zimbabwe. In 2000, the number of academic staff was 87, and then reached 320 in 2005 against a projected number of 223. This number increased to 434 in 2010 against a projection of 430. This rise in the number of the academic staff was against the background of the brain drain as a result of the economic meltdown which the whole country experienced between 2005 and 2009. This paper, therefore, explores the talent and skills attraction and retention strategies employed by MSU during the decade of its existence. A documentary analysis in which the MSU Strategic and Business plans, Human Resource (HR) plans and payrolls were analyzed is used. This was coupled with unstructured interviews with the university Registrars and staff representatives. The results showed that there was a conscientious effort by the university to attract and retain the required skills. Above all, the open door policy of engaging management and the clearly defined promotion and tenure policies made the stay at MSU for the academic staff pleasant.